Multiple time series models - Brandt, Patrick T. (Quantitative applications in the social sciences ;, 2007)
A comprehensive introduction to multiple time series in the social sciences, this book places multiple time series into historical context and then introduces structural equation modeling, vector auto regression (VAR), and factor analytic techniques for analysing multiple time series.